Mineralogical evidence of heating events in Antarctic carbonaceous chondrites, Y-86720 and Y-82162 - Akai, Junji (National Institute of Polar Research, 1990)
P(論文) Antarctic carbonaceous chondrites, Y-82162 and Y-86720 were examined by transmission electron microscopy. Matrix phyllosilicates in both meteorites are probably serpentine and saponite. There is evidence that these phyllosilicates were affected by thermal metamorphism. The serpentine was almost completely transformed to olivine or an intermediate phase between serpentine and olivine. The degrees of thermal metamorphism in Y-86720,Y-82162 and Y-793321 were compared, and heating experiments of terrestrial saponite and Murchison CM chondrite were also carried out for detailed comparison. Based on these observations and experiments, estimated degrees are as follows : Y-86720>Y-82162>Y-793321. departmental bulletin paper